Role of Social Support and Self-Concept Clarity as Predictors on Thesis Writing Procrastination - Rahmat Fitrah Tuasikal; Bhina Patria (Journal of Psychology and Instruction, 2019)
Procrastination is a behavior to delay the completion of the task. The postponement also occurred among students of Master of Psychology Program, at Gadjah Mada University. Students exceeded their study time and have not been able to complete their thesis. The purpose of the study was to find out the role of social support, and self-concept clarity as a predictor of thesis writing procrastination behavior. The subject of this research was 115 students. Three scales used to collect the data, were social support scale, self-concept clarity scale, and thesis writing procrastination scale. As conclusion this finding suggests that social support and self-concept clarity may predict thesis writing procrastination, the higher level of social support and self-concept clarity may account for the lower thesis writing procrastination both simultaneously and partially. These findings underscore the importance of social support and self-concept clarity as buffers against the thesis writing procrastination. The category scores obtained by procrastination of thesis writing tend to be moderate, social support tends to be high and self-concept clarity tends to be moderate.